2013
DOI: 10.1044/1058-0360(2013/12-0085)
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Bilingual Aphasia: Evidence for Within- and Between-Language Generalization

Abstract: Purpose The goal of this project was to examine if there was a principled way to understand the nature of rehabilitation in bilingual aphasia such that patterns of acquisition and generalization are predictable and logical. Methods Seventeen Spanish-English bilinguals with aphasia participated in the therapy experiment. For each participant, three sets of stimuli were developed for each language: (a) English Set 1, (b) English Set 2 (semantically related to each item in English Set 1), (c) English Set 3 (unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
73
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 47 publications
16
73
3
4
Order By: Relevance
“…Therefore, during the course of rehabilitation, training items in one language would be predicted to result in crosslanguage generalization to untrained items. This would be consistent with our previous work (Edmonds & Kiran, 2006;Kiran & Iakupova, 2011;Kiran & Roberts, 2010;Kiran et al, 2013) in which treatment resulted in cross-language generalization to translations and neighbours, in addition to improved access to trained items and within-language generalization to semantically related neighbours. It is possible, however, that after brain damage the cognitive control network may work imperfectly, resulting in suboptimal nonlinguistic control abilities.…”
Section: Aims Of the Current Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, during the course of rehabilitation, training items in one language would be predicted to result in crosslanguage generalization to untrained items. This would be consistent with our previous work (Edmonds & Kiran, 2006;Kiran & Iakupova, 2011;Kiran & Roberts, 2010;Kiran et al, 2013) in which treatment resulted in cross-language generalization to translations and neighbours, in addition to improved access to trained items and within-language generalization to semantically related neighbours. It is possible, however, that after brain damage the cognitive control network may work imperfectly, resulting in suboptimal nonlinguistic control abilities.…”
Section: Aims Of the Current Studysupporting
confidence: 91%
“…Patients received a semantic-based naming treatment in one language (either English or Spanish), and cross-language generalization was examined to the untrained language (Kiran, Sandberg, Ascenso, Kester, & Gray, 2013). Most of the patients showed within-language generalization (i.e., generalization to semantically related items within the same language), a finding that is consistent with theories of monolingual aphasia rehabilitation (Kiran & Bassetto, 2008;Maher & Raymer, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…In the category of general treatments, three studies focused on testing the effectiveness of specific treatments in different language abilities [26][27][28] . All samples were formed by a similar number of participants (10 to 19), with diagnoses of bilingual, chronic and non-fluent aphasia.…”
Section: Treatments With Repetitive Trans Cranial Electric Stimulatiomentioning
confidence: 99%
“…Despite the fact that conducting therapy in both languages has been advanced to facilitate language recovery (Ansaldo, Marcotte, Scherer, & Raboyeau, 2008;Kohnert, 2004), the general trend in aphasia rehabilitation still favours "monolingual" therapies (i.e., a therapy in one language) for the following reasons: (1) bilingual therapy has been argued to confuse the patient and lead to an increase in code mixing or code switching or that improvement occurs in only one of the treated languages (Edmonds & Kiran, 2006;Kiran, Sandberg, Gray, Ascenso, & Kester, 2013); (2) bilingual therapy can often not be provided due to practical limitations, and (3) based on evidence that in bilinguals the two languages usually share the same lexical and morphosyntactic representations (Gollan, Montoya, FennemaNotestine, & Morris, 2005), unilingual therapy may be the optimal approach to improve both languages in bilingual aphasic patients because crosslanguage treatment generalisation effects (CLG) should occur (Faroqi-Shah et al, 2010;Kohnert, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning cross-language generalisation patterns induced by semantic or phonological therapies, semantic therapy has been reported to induce CLG in studies with bilingual aphasic patients (Croft, Marshall, Pring, & Hardwick, 2011;Edmonds & Kiran, 2006;Kiran et al, 2013;Kohnert, 2004;Miertsch, Meisela, & Isel, 2009). In contrast, although Hinckley (2003) and Marangolo et al (Marangolo, Rizzi, Peran, Piras, & Sabatini, 2009) showed some level of CLG with mixed semantic-phonological therapy or using phonological therapy in L2, CLG was not found after phonological therapy in Meinzer et al (Meinzer, Obleser, Flaisch, Eulitz, & Rockstroh, 2007), or transfer was limited to phonologically similar words (cognates) (Kohnert, 2004;Pillon & de Partz, 2005).…”
Section: Introductionmentioning
confidence: 99%